PERBEDAAN TINGKAT KECEMASAN IBU HAMIL PRIMIGRAVIDA DAN MULTIGRAVIDA TRIMESTER III DENGAN PERILAKU IBU DALAM MENGHADAPI PERSALINAN DI KLINIK BERSALIN SRI KESUMA STR. KEB - ekry binti farizal (Institut Kesehatan dan Teknologi Al Insyirah, 2020)
Anxiety happens in almost maternal, in society. People still have the paradigm if considering that birth is the survival of life and death, so that the women who will give a birth get seared and frightened. Based on the purpose of this research. I want to find the differentiation of anxiety level of maternal behavior primigravida and multigravida in trimester III with thw behaviour of maternal in faching birth in Klinik bersalin Sri Kesuma STr. Keb Pangkalan Kerinci 2014. Based on the taken November 2019 the amount of maternal visit in clinic sri kesuma str. keb in 2018 is 396. The kind of research is analitycal and the design is cross sectional based on accidental sampling. It is used the frequency distribution and chi-square of statistical analytic. The result of this research is 66 maternal, 33 maternal of primigravida wich answered the quisioner (66,7%) including anxiety and negative behaviour is (54,5%) mean while the 33 maternal of multigravida wich got anxiety is (51,5%) with positive behaviour (57,6%). Based on the result of this research, most of maternal primigravida is got anxiety more with negative behaviour than maternal of multigravida with positive behaviour. Regarding that result, it is need the medical staff to give the information and midwifery especially to maternal of primigravida related to maternal behaviour in facing birth.